Voltage-gated sodium channels: structure, function and channelopathies - Chahine, Mohamed (Handbook of experimental pharmacology, 2018)
Intro -- Preface -- Contents -- Part I: Evolution of Voltage-Gated Sodium Channels -- Evolutionary History of Voltage-Gated Sodium Channels -- 1 Introduction -- 2 Structural Outlines of Voltage-Gated Sodium Channels -- 3 Historical Origin of Voltage-Gated Sodium Channels and Their Related Proteins -- 4 Evolution of Bilaterians and Voltage-Gated Sodium Channel Proteins -- 5 Voltage-Gated Sodium Channels in Chordates -- 6 Evolution of NaV1 Channels in Vertebrates -- 7 Independent Gene Duplications of NaV1 in Teleosts and Amniotes -- 8 Concluding Remarks -- References -- Mining Protein Evolution for Insights into Mechanisms of Voltage-Dependent Sodium Channel Auxiliary Subunits -- 1 Sodium Channel Basics -- 2 VGSC and Human Disease -- 3 β-Subunit Homology from the Perspective of Primary Sequence -- 4 Evolutionary History of Beta-Subunits -- 5 Structural Features and Regions of Sequence Conservation -- References -- Part II: The Structural Basis of Sodium Channel Function -- Structural and Functional Analysis of Sodium Channels Viewed from an Evolutionary Perspective -- 1 Introduction -- 2 The Voltage-Sensing Module -- 2.1 The Excitable Membrane and the Voltage Sensor -- 2.2 A Conserved Mechanism of Activation -- 3 The Selectivity Filter: From Symmetry to Asymmetry -- 4 Inactivation Evolved from Bacterial to Eukaryotic Sodium Channels -- 4.1 Slow Inactivation of Eukaryotic Sodium Channels -- 4.2 Studies of Slow Inactivation of Bacterial Sodium Channels -- 4.3 Evolution of Fast Inactivation in Eukaryotic Sodium Channels -- 5 Modulation of Sodium Channels by Their C-Terminal Tail -- 6 Conclusion -- References -- The Cardiac Sodium Channel and Its Protein Partners -- 1 Introduction -- 2 Specialized Membrane Domains in Cardiac Sarcolemma -- 2.1 Intercalated Disk -- 2.2 Lateral Membrane -- 2.2.1 Costamere -- 2.2.2 T-Tubule System.